Transition-metal- and oxidant-free three-component reaction of quinoline N-oxides, sodium metabisulfite and aryldiazonium tetrafluoroborates via a dual radical coupling process. Issue 43 (25th October 2019) - You, Guirong; Xi, Dan; Sun, Jian; Hao, Liqiang; Xia, Chengcai
Abstract : Synthesis of 2-sulfonylquinolines via a three-component reaction of quinoline N -oxides, sodium metabisulfite, and aryldiazonium tetrafluoroborates under transition-metal- and oxidant-free conditions. Abstract : A convenient and straightforward three-component transformation of quinoline N -oxides, sodium metabisulfite and aryldiazonium tetrafluoroborates has been developed, providing the target products in moderate to good yields. Compared with previous studies, the present methodology avoids the use of transition-metal catalysts and excess oxidants, providing a simple and practical alternative approach for the construction of 2-sulfonylquinolines. Control experiments indicate that a dual radical coupling process is responsible for this reaction.